Intervención del terapista respiratorio en neumonía intersticial usual en paciente masculino de 70 años de edad. - Morejón Murillo, Jeniffer Suggeydy (2022)
This case study shows us a usual interstitial pneumonia in a 70 year male patient, admitted to the emergency unit with symptoms of urgent type pain located in the bilateral posterior hemithorax, which is accompanied by chronic cough, increased dyspnea on slight exertion, paroxysmal nocturnal dyspnea, and orthopnea. The patient arrived with very poor respiratory mechanics, for which the order was given to channel a peripheral route and place oxygen at 9 lpm through a simple mask. The diagnosis was confirmed with a chest tomography in which the presence of a predominantly subpleural honeycomb pattern, traction bronchiectasis in the mediastinal window, and a dilated esophagus were observed, leading to the conclusion that the patient had interstitial pneumonia. usual. The treatment was with respiratory therapy and medication, receiving discharge after 4 days of intervention.